Transtorno do Desenvolvimento da Coordenação em adolescentes e sua relação com o desempenho de leitura e escrita - Bontempo, Kaíla da Silva (2020)
The literature indicates out that part of the students with learning difficulties has a disorder in the development of motor coordination. In children and adolescents, coordination disorders can be expressed from deficits in the acquisition and execution of coordinated motor skills, without these presenting any type of neurological or structural impairment (congenital disabilities, mental retardation or physical disability). These disorders are defined as Coordination Development Disorder (DCD). This study has the general objective of identifying signs indicating DCD in adolescents from the 6th and 7th years of elementary school and correlating them with reading and writing skills. This is a descriptive research - exploratory and correlational, of a transversal character, enabling quantitative and qualitative analyzes. It was carried out at a municipal school in Uberaba - MG, drawn by means of Excel's “random among” function. The sample consisted of those who agreed to sign the informed consent form and thus participate in the research. The DCDQ - BR instrument was answered by the parents of 23 adolescents, evaluated by the motor performance instruments, DCDQ - BR and mABC - II. The results showed that the majority of adolescents evaluated by their parents using the DCDQ - BR instrument were identified with DCD, reaching a score ≤57 points. Regarding mABC-2, five were identified with probable DCD. The final sample consisted of 3 adolescents, identified with DCD in the two instruments mentioned above. Of these, all participants showed impairment in reading and writing skills, according to the instruments of School Performance Test and Test of Competence in Reading Words and Pseudowords . The teenager who had more difficulty in school performance was the one who obtained the lowest score on motor tests, which reinforces the correlation proposed in this study. In addition, the adolescents assessed themselves through the Game of Incomplete Sentences and the teachers assessed the motor, school and behavioral performance of the three participants through an interview. All participants agreed to have poor academic performance in reading and writing; good motor performance and good social performance at school. For teachers, only one student of the evaluated has significant difficulty in reading and writing skills. The analysis of qualitative data was based on the Human Occupation Model.